Efficacy and Safety of Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors as Adjuvant Treatments for Patients with Hypercholesterolemia Treated with Statin: A Systematic Review and Network Meta-analysis - Huang, Yi-Ting; Ho, Li-Ting; Hsu, Hsin-Yin; Tu, Yu-Kang; Chien, Kuo-Liong (Frontiers in Pharmacology, 2022)
Background: The proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors are potent LDL-C lowering agents. However, few head-to-head studies evaluated the efficacy on the lowering in other atherogenic apolipoproteins and safety of PCSK9 inhibitors at different dosages as an add-on statins therapy in hypercholesterolemia patients. Methods: This study is a systematic review and network meta-analysis of randomized control trials to compare the efficacy of lipid reduction and adverse events (AE) of PCSK9 inhibitors in statin-treated hypercholesterolemia patients. PubMed, EMBASE, and Cochrane Library databases were searched till April 20, 2021, for randomized controlled trials. Random-effect network meta-analyses were undertaken to compare the differences in the percent reduction in low-density lipoprotein cholesterol (LDL-C), apolipoprotein B (ApoB), and lipoprotein(a) [Lp(a)] levels, and the risk of AEs among different PCSK9 inhibitors. Results: A total of 22 articles with 42,786 patients were included. The lipid reductions in LDL-C, ApoB and Lp(a) with add-on PCSK9 inhibitors vs. placebo in statin-treated patients across all trials were 50% to 63%, 43% to 52% and 23% to 31%, respectively. Evolocumab 140mg Q2W was ranked the best among all treatment strategies for lowering LDL-C, ApoB and Lp(a) levels and the treatment difference was -68.05% (95% confidence interval (CI), -73.67% to -62.43%) in LDL-C reduction, -54.95% (95% CI, -60.35% to -49.55%) in ApoB reduction and -34.25% (95% CI, -40.91% to -27.59%) in Lp(a) reduction compared with placebo. No significant risk difference of adverse events between PCSK9 inhibitors and placebo was found. Conclusions: PCSK9 inhibitors showed a significant effect on the reduction in LDL-C, ApoB and Lp(a) levels in statin-treated patients. Evolocumab 140mg Q2W showed significantly larger degrees of LDL-C, ApoB and Lp(a) reduction.